UPAYA PENINGKATAN PENGETAHUANRUMAH SEHAT BAGIKELUARGA - Arif Fajar Wibisono (Asian Journal of Innovation and Entrepreneurship, 2014)
DusunDeles,Jogonayanvillage, DistrictNgablak, Magelang, Central Javaconsistingof 3 RW and 12 RT.Mostly livelihood society is a farmer. Besides his profession as afarmer, society Also worked as traders, civil servants, workers, etc. People in theDusunDeles ispeople who have a high desire to advance Dusun Deles,this can be proved onthe willingness of citizens to cooperate and worked- together for development inDusun Deles.Deles people's lives are still very simple also influential in community awarenessabout environmental health, especially in the management of houses by the residentsthemselves. Many livestock barns which is still the one with the house causes dirtyhouse.